Luxury Spaces and the Five Senses: the Impact of Sensory Marketing on Customer Experience in Luxury Retail - Enwo, Orieoma A. O. (2019)
Traditionally, luxury has not been easily accessible to the mass due to unique distribution and pricing conventions. This has not changed even with the rise of online shopping; managers of luxury fashion brands who prioritise customer experience continue to advocate for physical retail stores. Research has shown that the five senses have significant impact on emotions; inferring that brands can appeal to consumers through sensory stimuli. Therefore, this dissertation explores the relationship between sensory marketing and customer experience within luxury retail settings, focusing specifically on the effect of holistic sensory approaches versus individual uses. In this context, customer experience has two dimensions: participation and connection (Pine and Gilmore, 1998). This research also aims to determine whether the overall experience influences the perceived value of a luxury brand. After an extensive review of academic literature to establish the current understanding of each specialised area, this research follows a similar study by conducting several in-depth interviews in an attempt to gain insight into the mindset of consumers whilst shopping. A qualitative analysis of the interview responses was completed so as to discover various patterns that could be linked back to the wider discussion surrounding participants’ shopping experiences. A key pattern revealed that multisensory stimuli are capable of positively affecting consumers’ emotions, thus influencing their levels of participation and connection. However it is important for the stimuli to be utilised in a cohesive manner that also aligns with the brand’s image. Moreover, a memorable experience will influence the way in which consumers perceive brand value. Interestingly, a prominent theme derived from the data revealed that service quality - specifically store employees- also plays a focal role in sensorial experiences. Since this discovery extends the scope of this research, further investigation should be taken in order to identify the extent of its effectiveness. Ultimately, these findings should raise awareness amongst practitioners on the ways in which to elevate brand experiences and strengthen retail presence in the fashion sector.